Photodegradation of a semi-aromatic bio-derived polyimide. (February 2021) - Mai, Anh Thi Minh; Thakur, Ashutosh; Ton, Nhan Nu Thanh; Nguyen, Thanh Nhat; Kaneko, Tatsuo; Taniike, Toshiaki
Highlights: A photodegradation study of a novel bio-derived and optically transparent polyimide was conducted. IR data analyses by spectral expression of correlation coefficients and NMR spectroscopy were used to understand degradation mechanisms. The material was chemically stable up to several hundreds of hours of photoirradiation. Photodegradation happened at the position of the cyclobutane, imide, and aromatic groups. Abstract: Recently, we have developed a thermoelectrically superior and highly transparent bio-derived polyimide using microorganism-derived 4-aminocinnamic acid. Here, the stability of the novel bio-derived polyimide under photoirradiation was systematically investigated. Infrared spectroscopy (IR), solid-state nuclear magnetic resonance (NMR), and tensile tests were employed for studying the impacts of the irradiation on both chemical and mechanical properties of the material. The structural modifications of the material were analyzed in the form of spectral expression of correlation coefficients. It was found that the bio-derived polyimide maintained its stability well up to several hundreds of hours. Elongated radiation caused deterioration at the imide ring and the tertiary carbon of the cyclobutane ring, accompanied by the growth of carbonyl species as an oxidation product.